2000
DOI: 10.1128/.38.6.2181-2185.2000
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Low-Level Bacteremia in Children from Birth to Fifteen Years of Age

Abstract: A single blood culture inoculated with a small volume of blood is still frequently being used for the diagnosis of bacteremia in children because of the continued belief by many that bacteria are usually found in high concentrations in the blood of pediatric patients with sepsis. To determine the importance of both blood volume cultured and the number of culture devices required for the reliable detection of pathogens in our pediatric population, blood from children from birth to 15 years of age and with suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 23 publications
0
35
0
1
Order By: Relevance
“…[ 4 , 19 , 35 , 38 , 39 ] Blood cultures can only be positive if there is bacteremia at the time the blood is drawn and if sufficient blood is examined. [ 42 , 43 ]In our study, the amount of blood examined for bacteria may have been insufficient. In another study, negative blood culture was found in osteomyelitis patients with small bones and/or non-staphylococcal disease.…”
Section: Discussionmentioning
confidence: 90%
“…[ 4 , 19 , 35 , 38 , 39 ] Blood cultures can only be positive if there is bacteremia at the time the blood is drawn and if sufficient blood is examined. [ 42 , 43 ]In our study, the amount of blood examined for bacteria may have been insufficient. In another study, negative blood culture was found in osteomyelitis patients with small bones and/or non-staphylococcal disease.…”
Section: Discussionmentioning
confidence: 90%
“…Bacteremia patients generally have <5 cfu of bacteria per milliliter of blood (33). Two studies by Kellogg et al found that low-level bacteremia, <1 cfu/ mL, was responsible for 71% and 75% of pediatric deaths owing to sepsis (34,35). With so few bacteria per milliliter of blood, we can see how easily bacteremia can be missed if a small volume is sent for culture.…”
Section: Blood Culturementioning
confidence: 98%
“…Inadequate blood used to inoculate blood culture bottles, small colony counts, intermittent bacteremia, and maternal administration of antibiotics are plausible explanations for false-negative blood cultures in these symptomatic neonates. 2,[20][21][22] Neonatal caregivers often have to rely on their nonspecific subjective evaluation, hemodynamic instability, respiratory distress/apnea, poor feeding, and laboratory findings such as leukocytosis/leukopenia, elevated CRP, abnormal IT ratio, low platelet count, and hypo/hyperglycemia to guide their management. 2 There is no single test which can predict clinical sepsis if the blood culture is negative.…”
Section: Discussionmentioning
confidence: 99%